In vitro growth of mouse preantral follicles: effect of animal age and stem cell factor/insulin-like growth factor supplementation - Jee, Byung Chul (The Korean Society for Reproductive Medicine, 2012)
OBJECTIVE: To determine whether animal age impacts in vitro preantral follicle growth. Effects of hCG, stem cell factor (SCF), and/or insulin-like growth factor (IGF) supplementation in growth medium were also investigated. METHODS: Intact preantral follicles were mechanically isolated from fresh ovaries of BDF1 mice and cultured in growth medium for 9 to 11 days. Surviving follicles with antrum formation were transferred to maturation medium for 14 to 18 hours. Follicle survival, antrum formation, and retrieval of metaphase II (MII) oocytes were compared among three age categories (4-5, 7-8, and 10-11 week-old). By using 7- to 8-week-old mice, preantral follicles were cultured in growth medium supplemented with hCG (0, 5, or 10 mIU/mL), SCF (50 ng/mL), IGF-1 (50 ng/mL), and SCF+IGF-1. RESULTS: Seven- to eight-week-old mice showed a higher follicle survival and antrum formation and produced more MII oocytes compared to other groups. In the 7- to 8-week-old mice, supplementation of 5 mIU/mL hCG significantly enhanced the antrum formation but the percentage of MII oocytes was similar to that of the control. Supplementation of SCF+IGF-1 did not enhance follicle survival or antrum formation but the percentage of MII oocytes increased modestly (39.1%) than in the control (28.6%, statistically not significant). CONCLUSION: Seven- to eight-week-old mice showed better outcomes in growth of preantral follicles in vitro than 4- to 5- or 10- to 11-week-old mice. Supplementation of hCG enhanced antrum formation and supplementation of SCF+IGF-1 yielded more mature oocytes; hence, these should be considered in the growth of preantral follicles in vitro.